A new intra-aerobic metabolism in the nitrite-dependent anaerobic methane-oxidizing bacterium Candidatus 'Methylomirabilis oxyfera'. (19th January 2011) - Wu, Ming L.; Ettwig, Katharina F.; Jetten, Mike S.M.; Strous, Marc; Keltjens, Jan T.; Niftrik, Laura van
Abstract : Biological methane oxidation proceeds either through aerobic or anaerobic pathways. The newly discovered bacterium Candidatus 'Methylomirabilis oxyfera' challenges this dichotomy. This bacterium performs anaerobic methane oxidation coupled to denitrification, but does so in a peculiar way. Instead of scavenging oxygen from the environment, like the aerobic methanotrophs, or driving methane oxidation by reverse methanogenesis, like the methanogenic archaea in sulfate-reducing systems, it produces its own supply of oxygen by metabolizing nitrite via nitric oxide into oxygen and dinitrogen gas. The intracellularly produced oxygen is then used for the oxidation of methane by the classical aerobic methane oxidation pathway involving methane mono-oxygenase. The present mini-review summarizes the current knowledge about this process and the micro-organism responsible for it.